THE INFLUENCE OF THE QUALITY OF SERVICE TO LIBRARY VISITORS SATISFACTION (Study in The Library IAIN Batusangkar) - Tri Yuliani (IAIN Batusangkar, 2018)
The library is one of sources of information have an important role in the field of management and the dissemination of information.Good service to visitors library would increase satisfaction visitors.The purpose of this research is to know the influence of library services against satisfaction visitors in the library iain batusangkar and library services most dominant against satisfaction visitors.The quality of service can be seen from a tangible (evidence physical) , the reliability of) reability (the responsiveness of responsiveness (the responsiveness of) assurance life for you and empathy (empathy ) that could be met. By increasing the quality of service that this will create visitor satisfaction, but the importance of a the quality of services in the library libraries are not balanced with the facilities and infrastructures good. Data sources used was the data to the spread of the kuisioner primary.The sample of the by 80 in total.This research result indicates that all the variables influential together to satisfaction visitors.Haphazardly variable assurance and emphaty can provide the effect on satisfaction visitors, while variable tangible, reability and responsiveness not to exert an influence upon satisfaction visitors in the library IAIN Batusangkar. The result of this research that is indicative of the value of the coefficients of determination as much as 31,2 % , so there were thousands of visitors satisfaction in drinking water has in addition to being influenced by the quality of service have also been influenced by another aspect 68,8 % , it is expected that there have been instances of advanced research to make a statement on another aspect that capable of affecting of satisfaction visitors in working the library IAIN Batusangkar